A Review Paper on Enhancement of Process Parameters for CNC Turning Of Stainless Steel Utilizing a Coated Tool - Sushmit Kumar Diwakar; Mr. Abhinav Kumar (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
The global environmental awareness is increased, and environmental regulations become more stringent, the negative effects of cutting fluids on the environment are becoming more apparent. At present, in high-productivity manufacturing enterprises, the supply, maintenance and recycling costs of cutting fluids account for 13%-17% of the manufacturing cost of the workpiece. In Computer Numerical Control turning of hard materials such as steels, cast iron and super alloys, involves high cutting forces, leads to more power consumption and decreasing tool life which may increases the machining cost. To make machining process environment friendly with minimizing cost of machining, dry cutting is the best solution. This work aimed to optimize the most influencing process parameters to minimize cutting forces and surface roughness in CNC turning of hard bearing material AISI 52100 and to develop predictive model of surface roughness.